Facile approaches to designing pits on acetabular cups using copper electrodes in die sinking electrical discharge machining - Norzahir, Sapawe; Syahrullail, Samion; Md Razak, Daud; Muhammad Farhan, Hanafi (Elsevier Ltd., 2018)
This study investigates the wear on copper electrodes and the size of the micro-pits or micro-holes that are produced, after using an Electrical Discharge Machining (EDM) die sinking system. A copper electrode Ø 0.2 mm, and a model of an acetabular cup made from tool steel (SKD11), were used. The results show that electrode wear is greater when higher currents are applied. The current discharges applied were 0.5 A, 1.5 A, and 3.0 A, and they resulted in electrode wear of 0.236 mm, 0.246 mm, and 0.269 mm respectively. The highest mean area of the pits machined, at approximately 65901.9 μm2, was observed for the application of a 3.0 A current. Therefore, the EDM die sinking system could be a useful method for surface modification